NON-LINEAR FINITE ELEMENT MODELING OF MECHANICAL BEHAVIOR OF SINGLE-WALLED CUBIC ZIRCONIA NANOTUBES. - DAUDA MUHAMMAD, IBRAHIM (2015)
Due to some unique properties, zirconia nanotube is one of the inorganic nanotubes that are attracting interest because of its structural capabilities with wide scale potential applications. However information on some mechanical properties of zirconia nanotubes is not readily available and difficult to determine due to several constraints. In this study, first principles calculations based on molecular dynamics was used to predict the bulk mechanical properties of Zr02 which were later utilized as input data for continuum analysis. Multilinear Isotropic Hardening model was used to develop the 3D structures of zirconia nanotubes having different chirality and were exposed to different boundary conditions for non-linear finite element analysis. The simulated results vary with the zigzag nanotubes having the optimum properties and were inversely proportional to the diameter, length and thickness.